2014
DOI: 10.5339/gcsp.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Improved understanding of the pathophysiology of atrial fibrillation through the lens of discrete pathological pathways

Abstract: Atrial fibrillation (AF) is a common disorder with a complex and incompletely understood pathophysiology. Genetic approaches to understanding the pathophysiology of AF have led to the identification of several biological pathways important in the pathogenesis of the arrhythmia. These include pathways important for cardiac development, generation and propagation of atrial electrical impulses, and atrial remodeling and fibrosis. While common and rare genetic variants in these pathways are associated with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…Valvular abnormalities, hypertension, and diabetes have been associated to AF. Actually, genetics and molecular pathways are deeply involved in the development of the disease [101]. …”
Section: Methodsmentioning
confidence: 99%
“…Valvular abnormalities, hypertension, and diabetes have been associated to AF. Actually, genetics and molecular pathways are deeply involved in the development of the disease [101]. …”
Section: Methodsmentioning
confidence: 99%
“…Polidoro (24)(25)(26). Cross-sectional studies have shown that patients with prevalent AF have higher levels of CRP than age-matched controls (27,28). Longitudinal studies have shown that individuals with high levels of CRP are at risk for developing de novo incident AF (29).…”
Section: Implications Of Frailty For Af Carementioning
confidence: 97%
“…[12][13][14] Despite the importance of both genetic predisposition and atrial fibrosis in the pathophysiology of AF, little is known about how these two factors relate or interact with one another. 15,16 For example, it is unknown if genetic variants promote substrate changes, such as atrial fibrosis. Furthermore, it is unknown whether atrial fibrosis is associated with higher risk of recurrent AF in patients with and without genetic predisposition to AF.…”
mentioning
confidence: 99%